A perovskite catalyst modified by waste lithium battery cathode powder and a preparation method and use thereof
Patent Information
- Application Number
- CN202410784846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-18
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-06-18
AI Technical Summary
[0006]本发明所要解决的技术问题是:针对目前生物质气化钙钛矿催化剂表面氧的缺乏,催化焦油裂解能力差,合成气产率低等问题,利用从废弃锂电池中回收的富锂阳极材料进行掺杂改性,制备一种在高温下拥有高氧化活性的生物质气化催化剂
[0020]本发明通过回收废弃锂电池中富含Li+与Co3+/Ni3+等的电极材料作为改性物质,添加进传统钙钛矿催化剂,以提升后者晶体表面的活性氧位点数量,从而解决CO2活化能力弱,催化性能局限等问题,同时提高氧传导能力,减少焦油产出并提高合成气产率。
Smart Images

Figure CN118719036B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation technology, specifically to a perovskite catalyst modified from waste lithium battery cathode powder, its preparation method, and its applications. Background Technology
[0002] To achieve overall carbon emission reduction, industrial technology upgrading, and environmental protection, China has set strict carbon neutrality targets. In traditional industries, syngas can be obtained through the reforming of natural gas and coal. However, due to the non-renewable nature of fossil resources and the urgent need for carbon emission reduction, syngas production is gradually shifting towards high-yield, green, and environmentally friendly carbon-negative alternatives, primarily based on the gasification of renewable biomass or waste biomass, in order to achieve sustainable syngas production.
[0003] In the biomass gasification process, a pyrolysis reaction first occurs at high temperature, releasing primary pyrolysis products and forming coke. The primary pyrolysis products are then decomposed into gaseous components with smaller relative molecular masses (such as CO, H2, CH4, C2H4, C2H2, etc.) under the oxidation of O2, CO2 and H2O, and the coke is oxidized to CO. During the feeding process, due to the high reaction temperature and short heat transfer time in the system, biomass gasification involves a large number of complex and closely interconnected thermochemical processes: volatiles continuously precipitate from the surface of the thermally decomposed material and polymerize to form pyrolysis gas rich in tar. After formation, the pyrolysis gas quickly comes into contact with the gasifying agent and undergoes a cracking reaction to generate short-chain hydrocarbons, CO, and H2. The cracking products further undergo various reactions (including methane dry reforming, methane steam reforming, methane cracking reaction, water-gas shift reaction, and reverse water-gas shift reaction) to generate syngas rich in CO and H2. The remaining material forms semi-coke products with certain activity, which react with the gasifying agent to generate CO. Since this process is a strongly endothermic process, it is relatively difficult to carry out. Therefore, only with the cooperation of a catalyst can the gasification efficiency be significantly improved.
[0004] Secondly, the pyrolysis products of biomass have relatively large molecular weights and high degrees of polymerization. When these molecules come into contact with gasifying agent molecules, hydrocarbons and aromatic organic compounds are prone to chain breaking, ring opening, and oxidation reactions. Long-chain molecules break down into smaller molecules, and double bonds and benzene rings are destroyed and oxidized. However, in this process, some tar will not be completely decomposed due to factors such as reaction temperature, residence time, and reactivity. Therefore, the products of direct gasification at high temperatures contain a large amount of viscous heavy oil components, which not only easily clog the operating equipment and pipelines but also indirectly reduce the total amount of hydrocarbon components in the gasification products. Therefore, it is necessary to use catalysts to reduce tar production during the gasification process.
[0005] Currently, catalysts exhibiting high redox catalytic activity in gasification reactions mainly exist in the form of composite metal oxides. Perovskite oxides are widely used in biomass conversion processes due to their high thermal stability, excellent oxygen transfer capacity, and highly tunable structure. However, the lack of oxygen on the surface of pristine perovskite oxides limits oxygen transfer activity, necessitating further modification to effectively improve their catalytic performance. Seeking high-performance and environmentally friendly modification methods has become an urgent need for researchers. Currently, due to the rapid development of new energy technologies and the energy storage industry, my country's lithium battery production is increasing year by year, but this has also accelerated the rate of lithium battery retirement. Faced with the problem of massive waste lithium batteries, only rational resource recycling can solve the problems of scarce resource waste and potential heavy metal pollution. Lithium battery cathode materials contain high-density Li elements. This alkali metal has a strong electron-donating ability and exhibits high catalytic activity in biomass gasification, and is usually widely studied in the form of alkali metal salts. However, the low cation stability of alkali metal salts makes them extremely prone to vaporization, resulting in loss of active components and a decline in catalytic performance. Previous studies have shown that confining alkali metals within the a-sites of the perovskite lattice can significantly suppress losses caused by evaporation, while an ordered structure can greatly improve the utilization efficiency of alkali metal cation sites. Therefore, using waste lithium battery cathode materials as active materials to modify traditional perovskites and enhance the biomass gasification process is a high-potential modification method that simultaneously achieves resource utilization and high value. Summary of the Invention
[0006] The technical problem this invention aims to solve is to address the issues of insufficient surface oxygen, poor catalytic tar cracking ability, and low syngas yield in current biomass gasification perovskite catalysts. This invention utilizes lithium-rich anode materials recovered from waste lithium batteries for doping and modification to prepare a biomass gasification catalyst with high oxidation activity at high temperatures. This catalyst features low preparation cost, strong catalytic cracking ability, and high tar decomposition rate. Furthermore, since part of the catalyst is modified using hazardous waste materials, it can simultaneously achieve the goal of waste resource reuse and valuable metal recovery, thus possessing significant environmental benefits.
[0007] To achieve the above objectives, according to one aspect of the present invention, a method for preparing a perovskite catalyst modified from waste lithium battery cathode powder is provided, comprising the following steps:
[0008] 1) Disassemble waste lithium batteries, immerse the disassembled black powder along with the anode and cathode in a dissolving agent until the organic binder is completely dissolved, then filter, wash, dry and collect the cathode powder. The dissolving agent is N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide or dimethyl sulfoxide.
[0009] 2) Inorganic metal compound A and inorganic metal compound B, along with the cathode powder collected in step 1), are mixed in water, and citric acid is added and stirred thoroughly to dissolve. The mixture is then heated and stirred until a sol is formed. After drying, a dry gel is obtained. Among them, inorganic metal compound A is at least one of calcium nitrate tetrahydrate, calcium nitrite tetrahydrate, and lanthanum nitrate hexahydrate, and inorganic metal compound B is at least one of nickel nitrate hexahydrate, nickel nitrite hexahydrate, nickel citrate monohydrate, ferric nitrate nonahydrate, ferric nitrite nonahydrate, and ferric citrate pentahydrate.
[0010] 3) Place the dry gel obtained in step 2) in a muffle furnace and calcine it at 400-550℃ to remove the remaining organic matter. Then, heat it to 700-900℃ for a second calcination to ensure complete crystal growth. After cooling, grind it to obtain the perovskite catalyst.
[0011] As a further preferred technical solution of the present invention, the waste lithium battery is a lithium cobalt oxide battery, a lithium manganese oxide battery, a lithium nickel oxide battery, a lithium nickel cobalt manganese oxide battery, or a lithium nickel cobalt aluminum oxide battery.
[0012] As a further preferred embodiment of the present invention, the following steps are included before step 2):
[0013] The cathode powder collected in step 1) is added to the leaching aid and stirred until the powder is completely dissolved. The insoluble particles are then separated by filtration. The leaching aid is a mixture of an acidic aqueous solution and hydrogen peroxide, wherein the acidic aqueous solution is an aqueous solution of citric acid, acetic acid, or malic acid. The mass fraction of the acidic aqueous solution is 15-25%, and the hydrogen peroxide in the leaching aid accounts for 3-5% of the total liquid volume.
[0014] As a further preferred technical solution of the present invention, in step 2), the molar ratio of metal A ions provided by inorganic metal A compound, metal B ions provided by inorganic metal B compound, and lithium ions provided by cathode powder is 1:1:0.1-0.5.
[0015] As a further preferred technical solution of the present invention, in step 2), after adding citric acid, the molar ratio of citric acid to total metal ions is 1.2-1.4:1.
[0016] As a further preferred technical solution of the present invention, in step 2), the temperature during heating and stirring is 75-85℃; the temperature during drying is 100-120℃, and the drying time is 24-36h.
[0017] As a further preferred technical solution of the present invention, in step 3), the initial calcination time is 2-3 hours and the secondary calcination time is 3-5 hours.
[0018] According to another aspect of the present invention, the present invention also provides a perovskite catalyst prepared by the above-described method.
[0019] According to another aspect of the invention, the invention also provides the use of a perovskite catalyst in biomass gasification.
[0020] This invention recycles Li-rich materials from waste lithium batteries. + With Co 3+ / Ni 3+ Electrode materials such as those used as modifiers are added to traditional perovskite catalysts to increase the number of active oxygen sites on the crystal surface of the latter, thereby solving problems such as weak CO2 activation ability and limited catalytic performance. At the same time, it improves oxygen conduction capacity, reduces tar production and increases syngas yield.
[0021] This invention recycles Li-rich materials from waste lithium batteries. + With Co 3+ / Ni 3+ Electrode materials such as lithium oxide cathode powder are used as modifiers in catalyst synthesis. Citric acid is used as a complexing agent to form a uniformly dispersed complex precursor from lithium oxide-rich cathode powder, followed by a high-temperature solid-state reaction to form a homogeneous and stable perovskite catalyst. This invention avoids the use of environmentally harmful traditional leaching solutions such as sulfuric acid and hydrochloric acid in the extraction of valuable metals from spent lithium batteries. High temperatures are only used during catalyst calcination, making the entire process green and environmentally friendly. This not only solves the problem of large-scale disposal of spent lithium batteries but also develops a novel high-performance perovskite catalyst, achieving two goals at once. Furthermore, the preparation method of this invention combines the preparation of spent lithium battery cathode powder with the traditional sol-gel method, directly dispersing the spent battery powder in the thermally expanded dry gel. This greatly improves the dispersibility of the battery powder, reduces agglomeration, and increases the contact area with the nitrate precursor.
[0022] Extensive research has revealed that perovskite crystals exhibit an orthorhombic configuration, with two metals occupying the vertices (A) and center (B) sites, respectively. The element at site A primarily supports the overall perovskite crystal structure, while site B mainly acts as an oxygen conductor, becoming the active center of the catalyst. Because the perovskite catalyst lattice allows for a certain degree of distortion, this provides an opportunity for heteroatoms to enter the perovskite lattice and replace some of the A-site and B-site elements. Interestingly, cathode materials for "uni-lithium" and "ternary lithium" batteries, such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, or lithium nickel cobalt aluminum oxide batteries, contain a significant amount of Li₂, which can act as A-site substitution ions. + Co can act as a B-site substituent ion 3 + Ni 3+ Mn 3+Plasma, during high-temperature solid-state reactions, allows these ions to enter the perovskite lattice while maintaining the stability of the crystal.
[0023] The perovskite catalyst crystals modified by the method of this invention can form bimetallic compounds such as Ni-Co and Ni-Mn, thereby reducing the difficulty of electron transfer between metallic bonds and increasing the rate of active oxygen generation. Simultaneously, highly active Li-doped at the A-site metal... + It can enhance the overall electron-donating ability of the crystal lattice and increase surface alkalinity, thereby reducing the adsorption energy of gasifying agents such as H2O and CO2, promoting the activation ability of gasifying agent molecules, and rapidly completing the transfer process of active oxygen from gasifying agent to ions to primary pyrolysis products. The modified perovskite material can significantly improve the overall conversion efficiency of biomass, reduce the content of aromatic compounds and long-chain hydrocarbons in tar, and improve the yield and selectivity of the final syngas products. Attached Figure Description
[0024] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0025] Figure 1 The yield and carbon conversion rate of biomass CO2 gasification for different samples.
[0026] Figure 2 The total gas yield and syngas calorific value of biomass CO2 gasification for different samples.
[0027] Figure 3 Photographs of tar collected after CO2 gasification of different biomass samples.
[0028] Figure 4 The image shows the SEM microstructure of the catalyst prepared in Example 1.
[0029] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0030] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0031] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0032] Example 1
[0033] The preparation method of perovskite catalyst modified from waste lithium cobalt oxide battery cathode powder is as follows:
[0034] 1) Disassemble the waste lithium cobalt oxide battery, mechanically peel off the outer shell and remove the separator and tabs, collect the black powder, and immerse it together with the anode and cathode in N-methyl-2-pyrrolidone. Soak it at 80°C for 5 hours, separate the lithium cobalt oxide battery cathode powder, rinse it with water and dry it at 105°C for 24 hours.
[0035] 2) Take 2 parts by weight of lithium cobalt oxide battery cathode powder, 12 parts by weight of nickel nitrate hexahydrate, and 16 parts by weight of lanthanum nitrate hexahydrate and mix them in water. Add 21 parts by weight of citric acid and stir and heat continuously at 80°C until a sol is formed. Then transfer it to an oven and dry it at 105°C for 24 hours. After that, take out the dry gel and break it up for later use.
[0036] 3) The dry gel was placed in a muffle furnace and calcined at 550°C for 2 hours. Then, it was heated to 850°C and calcined for 5 hours. The calcined product was taken out and thoroughly ground to complete the preparation, thus obtaining the LaNiO3 catalyst modified with lithium cobalt oxide battery cathode powder.
[0037] Example 2
[0038] The preparation method of perovskite catalyst modified from spent nickel-cobalt-manganese lithium oxide battery cathode powder is as follows:
[0039] 1) Disassemble the waste nickel cobalt manganese lithium oxide battery, mechanically peel off the outer shell and remove the separator and tabs, collect the black powder, and immerse it together with the anode and cathode in dimethylformamide. Soak it at 90°C for 5 hours. Then collect the separated nickel cobalt manganese lithium oxide battery cathode powder, rinse it with water and dry it at 110°C for 36 hours.
[0040] 2) Take 2 parts by weight of lithium nickel cobalt manganese oxide battery cathode powder, 11 parts by weight of nickel nitrate hexahydrate, and 14 parts by weight of calcium nitrate and mix them in water. After dissolving completely, add 21 parts by weight of citric acid and dissolve completely. Heat at 90°C until a sol is formed. Then transfer to an oven and dry at 110°C for 24 hours. Remove the dry gel and break it up for later use.
[0041] 3) The dry gel was placed in a muffle furnace and calcined at 500°C for 3 hours. Then, it was heated to 900°C and calcined for 6 hours. The calcined product was taken out and thoroughly ground to complete the preparation, thus obtaining the CaNiO3 catalyst modified with nickel cobalt manganese oxide lithium battery cathode powder.
[0042] Example 3
[0043] The preparation method of perovskite catalyst modified from spent nickel-cobalt-manganese lithium oxide battery cathode powder is as follows:
[0044] 1) Disassemble the waste nickel cobalt manganese lithium oxide battery, mechanically peel off the outer shell and remove the separator and tabs, collect the black powder, and immerse it together with the anode and cathode in dimethyl sulfoxide for 5 hours at 90°C. Collect the separated nickel cobalt manganese lithium oxide battery cathode powder, rinse it with water and dry it at 115°C for 24 hours.
[0045] 2) Take 2 parts by weight of lithium nickel cobalt manganese oxide battery cathode powder, 15 parts by weight of iron nitrate, and 14 parts by weight of lanthanum nitrate hexahydrate and mix them in water. After dissolving completely, add 21 parts by weight of citric acid and dissolve completely. Heat at 80°C until a sol is formed. Then transfer to an oven and dry at 115°C for 36 hours. Remove the dry gel and break it up for later use.
[0046] 3) The dry gel was placed in a muffle furnace and calcined at 550°C for 2 hours. Then, it was heated to 750°C and calcined for 4 hours. The calcined product was taken out and thoroughly ground to complete the preparation, thus obtaining the LaFeO3 catalyst modified with nickel cobalt manganese oxide lithium battery cathode powder.
[0047] Comparative Example 1
[0048] As a control experiment of Example 1, cobalt nitrate and lithium nitrate were used as modifying materials to replace the lithium cobalt oxide battery cathode powder in step 2) of Example 1. The specific preparation method is as follows:
[0049] Take 12 parts by mass of nickel nitrate hexahydrate, 16 parts by mass of lanthanum nitrate hexahydrate, 5 parts by mass of cobalt nitrate hexahydrate, and 1 part by mass of lithium nitrate trihydrate (maintaining the same metal ion concentration as in Example 1). + Co 3+ Ni 3+ La 3+ The mixture (with consistent molar ratio) was completely mixed and fully dissolved. 21 parts by mass of citric acid were added and fully dissolved. The mixture was then heated at 85°C until a sol was formed. The sol was then transferred to an oven and dried at 100°C for 24 hours. The dried gel was then removed and crushed for later use. The dried gel was placed in a muffle furnace and calcined at 800°C for 5 hours. The calcined product was then thoroughly ground to complete the preparation, yielding a lithium-ion and cobalt-ion-doped LaNiO3 catalyst.
[0050] The catalyst samples prepared in Examples 1-3 and Comparative Example 1 were used to test the catalytic effect of biomass CO2 gasification, as follows:
[0051] The catalytic effect experiment was conducted in a vertical fixed-bed quartz reactor. The experimental gases were supplied by nitrogen cylinders (99.999%) and carbon dioxide cylinders (99.99%). Two gas washing bottles containing acetone and one gas washing bottle containing color-changing silica gel were placed at the rear end of the reactor. The catalyst samples prepared in Examples 1-3 and Comparative Example 1 were tested according to the following steps: 1g of catalyst sample and 1g of coconut shell biomass were thoroughly ground and mixed in a mortar; the reactor was preheated to 800℃ in a nitrogen atmosphere (100mL / min), and then switched to 100% CO2 for 20min to replace the nitrogen in the system; the reactants were added to the reactor and reacted for 1h. During this period, the generated gas was collected at the end of the gas washing bottle using a gas bag, and the gas composition was determined by gas chromatography after collection.
[0052] In the above experimental results, "original biomass" refers to the result obtained by directly gasifying the biomass sample without adding a catalyst; "original perovskite" refers to the result obtained by gasifying the biomass sample using the above test method with a perovskite catalyst without adding any modified substances. The preparation method of the perovskite catalyst is as follows: 12 parts by mass of nickel nitrate hexahydrate and 16 parts by mass of lanthanum nitrate hexahydrate are mixed in water, and 21 parts by mass of citric acid are added. The mixture is stirred and heated continuously at 80°C until a sol is formed. Then, it is transferred to an oven and dried at 105°C for 24 hours. The dried gel is then removed and crushed for later use. The dried gel is placed in a muffle furnace and initially calcined at 550°C for 2 hours, then heated to 850°C for 5 hours. The calcined product is then removed and thoroughly ground to complete the preparation.
[0053] The experimental results are attached. Figure 1 , 2 3. The results show that the perovskite modified with waste lithium battery cathode powder (Example 1) has higher performance than the perovskite modified with pure nitrate (Comparative Example 1), with a CO yield exceeding 1100 mL, H2 exceeding 300 mL, carbon conversion reaching 95%, and a calorific value of over 6 MJ / m³ in the product. 3 Furthermore, it significantly reduces the proportion of tar in the product. This demonstrates that the catalyst in Example 1 of this invention possesses superior catalytic performance and can effectively catalytically crack macromolecules in biomass into syngas. Compared to Example 1, Examples 2 and 3 use cathode powders from different waste lithium batteries as modifying materials, and the catalysts prepared also exhibit superior catalytic performance.
[0054] The experimental results above show that the catalyst sample modified with waste materials in this invention exhibits significantly better catalytic performance than the catalyst sample modified with pure nitrates. Because this invention uses waste lithium battery cathode powder as the modifying material, during the subsequent calcination process, the perovskite phase gradually forms a spherical shell coating the surface of lithium cobalt oxide, and cobalt and lithium ions from the lithium cobalt oxide at the contact points enter the perovskite lattice. Due to the difference in atomic radii between cobalt and lithium ions and the original lattice, the lattice is distorted to a limited extent, creating more defect sites on the crystal surface. Furthermore, cobalt ions form a bimetallic structure with the original perovskite B-site metal ions, greatly enhancing the transfer capacity of adsorbed oxygen on the metal bonds. The free movement of small-radius lithium ions between the lattice also promotes the enhancement of alkali-active sites on the perovskite surface, making it easier for reactants to adsorb onto the lattice surface and become activated. Simultaneously, the subsequent high-temperature calcination process directly decomposes the graphite and organic binder impurities in the original cathode powder, creating more porous structures between catalyst particles and promoting an increase in specific surface area. This inadvertently improves the catalyst's pore structure. The pore structure left after calcination and decomposition of carbon-based impurities is as follows: Figure 4 As shown.
[0055] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.
Claims
1. A method for preparing a perovskite catalyst modified from waste lithium battery cathode powder, characterized in that, Includes the following steps: 1) Disassemble waste lithium batteries, immerse the disassembled black powder along with the anode and cathode in a dissolving agent until the organic binder is completely dissolved, then filter, wash, dry, and collect the cathode powder. The dissolving agent is N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, or dimethyl sulfoxide. The lithium battery is a lithium cobalt oxide battery, a lithium manganese oxide battery, a lithium nickel oxide battery, a lithium nickel cobalt manganese oxide battery, or a lithium nickel cobalt aluminum oxide battery. 2) Inorganic metal A compound, inorganic metal B compound, and cathode powder collected in step 1) are mixed in water, citric acid is added and stirred thoroughly to dissolve, and then heated and stirred until a sol is formed. After drying, a dry gel is obtained. Among them, inorganic metal A compound is at least one of calcium nitrate tetrahydrate, calcium nitrite tetrahydrate, and lanthanum nitrate hexahydrate, and inorganic metal B compound is at least one of nickel nitrate hexahydrate, nickel nitrite hexahydrate, nickel citrate monohydrate, ferric nitrate nonahydrate, ferric nitrite nonahydrate, and ferric citrate pentahydrate. The molar ratio of metal A ions provided by inorganic metal A compound, metal B ions provided by inorganic metal B compound, and lithium ions provided by cathode powder is 1:1:0.1-0.
5. 3) Place the dry gel obtained in step 2) in a muffle furnace for initial calcination at 400-550℃, then raise the temperature to 700-900℃ for secondary calcination to ensure complete crystal growth. After cooling, grind to obtain the perovskite catalyst.
2. The method for preparing perovskite catalyst modified from waste lithium battery cathode powder according to claim 1, characterized in that, In step 2), the temperature during heating and stirring is 75-85℃, and the temperature during drying is 100-120℃.
3. The method for preparing perovskite catalyst modified from waste lithium battery cathode powder according to claim 1, characterized in that, In step 3), the initial calcination time is 2-3 hours, and the secondary calcination time is 3-5 hours.
4. A perovskite catalyst, characterized in that, It is prepared by the method described in any one of claims 1-3.
5. The application of the perovskite catalyst according to claim 4 in biomass gasification.
Citation Information
Patent Citations
Method for producing high-calorific-value combustible gas through in-situ catalysis of biomass pyrolysis volatile component
CN106391033A
Novel coke carbon dioxide gasifying catalyst and preparation method thereof
CN108097239A
Method for catalyzing biomass pyrolysis by using waste lithium battery-based metal modified catalyst
CN115558516A